Systemic Acute-phase Response in Laparoscopic and Open Ileal Pouch Anal Anastomosis in Patients With Ulcerative Colitis. Issue 5 (October 2015) - Okita, Yoshiki; Araki, Toshimitsu; Hiro, Junichiro; Ide, Shozo; Imaoka, Hiroki; Kondo, Satoru; Kawamura, Mikio; Fujikawa, Hiroyuki; Inoue, Mikihiro; Toiyama, Yuji; Ohi, Masaki; Tanaka, Koji; et al.
<x xml:space="preserve">Abstract</x> Aim: The current trial was designed to study and compare the postoperative outcomes and systemic acute responses between patients undergoing laparoscopic-ileal pouch anal anastomosis (LAP-IPAA) and open IPAA for ulcerative colitis. Methods: The clinical records of patients who underwent 89 restorative proctocolectomy procedures with IPAA were reviewed. After determining which patients underwent LAP-IPAA versus open IPAA, an equivalent number of controls matched for age and ulcerative colitis severity were selected. Results: Twenty of 22 patients who underwent laparoscopic surgery met the inclusion criteria. Patients who underwent LAP-IPAA had significantly shorter times to first walking (P=0.021) and food intake (P=0.0003). The LAP-IPAA group had significantly lower interleukin-6 and interleukin-1ra levels soon after surgery (P=0.011 and P=0.0076). The LAP-IPAA group had significantly lower C-reactive protein levels on postoperative day 1 (P=0.0027). Conclusions: LAP-IPAA is a less-invasive operative procedure than open IPAA with respect to the postoperative systemic inflammatory response and postoperative recovery.